Discourse Prominence and Antecedent Mis-Retrieval during Native and Non-Native Pronoun Resolution - Cecilia Puebla; Claudia Felser (Discours)
Previous studies on non-native (L2) anaphor resolution suggest that L2 comprehenders are guided more strongly by discourse-level cues compared to native (L1) comprehenders. Here we examine whether and how a grammatically inappropriate antecedent’s discourse status affects the likelihood of it being considered during L1 and L2 pronoun resolution. We used an interference paradigm to examine how the extrasentential discourse impacts the resolution of German object pronouns. In an eye-tracking-during-reading experiment we examined whether an elaborated local antecedent ruled out by binding Condition B would be mis-retrieved during pronoun resolution, and whether initially introducing this antecedent as the discourse topic would affect the chances of it being mis-retrieved. While both participant groups rejected the inappropriate antecedent in an offline questionnaire irrespective of its discourse prominence, their real-time processing patterns differed. L1 speakers initially mis-retrieved the inappropriate antecedent regardless of its contextual prominence. L1 Russian/L2 German speakers, in contrast, were affected by the antecedent’s discourse status, considering it only when it was discourse-new but not when it had previously been introduced as the discourse topic. Our findings show that L2 comprehenders are highly sensitive to discourse dynamics such as topic shifts, supporting the claim that discourse-level cues are more strongly weighted during L2 compared to L1 processing.